2012
DOI: 10.1292/jvms.11-0385
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Microphthalmia and Aphakia Associated with Multiple Eye Abnormalities in a Free-Living European Red Deer Calf (<i>Cervus elaphus</i>)

Abstract: ABSTRACT. A free-living European red deer calf (Cervus elaphus) was euthanized due to bilateral microphthalmia. Lens was missing, replaced by proliferating squamous epithelial cells; hyperplastic squamous cells, sebaceous and mucinous glands were observed within the cornea with the characteristics of inclusion cyst. Findings were consistent with congenital microphthalmia/aphakia, with multiple eye abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…In the case reported, all eye components were present bilaterally, with the exception of the lens of the left eye. Aphakia and retinal dysplasia have been reported to be associated with microphthalmia in a number of species including cattle5 17 34–36; however, the thickening of the sclera was a striking finding in this case. The presence of an abnormally thickened sclera has been reported in cases of microphthalmia in humans and it has been suggested that the abnormal collagen fibres may prevent the early development of the globe,37 although to our knowledge this has not been reported in cattle.…”
Section: Discussioncontrasting
confidence: 61%
“…In the case reported, all eye components were present bilaterally, with the exception of the lens of the left eye. Aphakia and retinal dysplasia have been reported to be associated with microphthalmia in a number of species including cattle5 17 34–36; however, the thickening of the sclera was a striking finding in this case. The presence of an abnormally thickened sclera has been reported in cases of microphthalmia in humans and it has been suggested that the abnormal collagen fibres may prevent the early development of the globe,37 although to our knowledge this has not been reported in cattle.…”
Section: Discussioncontrasting
confidence: 61%
“…Following displacement, the epithelium will proliferate and continuously deposit desquamated cells into the center of the cyst . These eye lesions have been previously reported in dogs, humans, llama, red deer, and a cat . The inciting cause can be trauma, previous corneal surgery, or these cysts can be congenital lesions .…”
Section: Introductionmentioning
confidence: 75%
“…1,3,4,10 These eye lesions have been previously reported in dogs, humans, llama, red deer, and a cat. [3][4][5][6]8,[10][11][12][13][14] The inciting cause can be trauma, previous corneal surgery, or these cysts can be congenital lesions. [1][2][3][4][5][6][7]10,12,[15][16][17][18][19] Affected eyes are typically comfortable with minimal associated keratitis, but vision can be impaired by the size and location of the cyst.…”
Section: Introductionmentioning
confidence: 99%
“…13,27 Similar congenital ocular defects to those described in humans and domestic animals have been sporadically reported in wild cervids, but underlying causes remain unknown. Cases in white-tailed deer (WTD) have been most frequently reported in the literature, 7,9,12,15,25,31 but reports of affected red deer (Cervus elaphus) 10,19 and moose (Alces alces) 14 are available. Specific findings in WTD have included unilateral and bilateral anophthalmia and microphthalmia, 7,9,12,25,31 cataracts, 12 retinal dysplasia, 9,12,31 colobomata, 12 and corneoscleral choristomas.…”
mentioning
confidence: 99%